An Eliminating Method to Improve Localization Accuracy. (12th June 2014) - Chen, Liangyin; Yan, Bingshu; He, Junjun; Zhang, Jingyu; Chen, Wen; Jiang, Yushi; Liu, Yan; Luo, Qian; Wang, Baoqiu
Node localization is essential in wireless sensor networks (WSNs). However, due to limited node energy and overhead network, node localization faces many challenges in WSNs. In addition, it is difficult to meet the requirement of localization accuracy and energy consumption at the same time in existing algorithms. In this paper, we proposed a novel eliminating algorithm called NPLA which achieves high localization accuracy and reduces energy consumption effectively. It makes full use of multiple-hop neighbor nodes of unknown node to eliminate the possible location area (PLA) of the unknown node. Simulations show that the localization error of algorithm NPLA can be controlled within 20%.